A three-month course of lamivudine therapy in HBeAg-positive hepatitis B patients with normal aminotransferase levels - Kendal YALÇIN,; Halil DEĞERTEKİN,; Ömer Faruk KOKOĞLU,; Celal AYAZ, (Turkish Journal of Gastroenterology, 2019)
-